PENGARUH AUTOGENIC DAN HANDGRIP RELAXATION TERHADAP ASPEK FISIKDAN ASPEK PSIKOLOGIS, PADA PENDERITA KANKER PAYUDARA YANG MENJALANI KEMOTERAPI - Dea Rosaline, Mareta; Agung Suprabawati, Desak; Endang Nihayati, Hanik (Unusa Press, 2017)
Women suffering breast cancer who undergo chemotherapy experience side effects both physical and psychological. Complementary therapy urgently needed for relaxing patient before chemotherapy such as Autogenic and Handgrip Relaxation through self-suggestion technique. This research aim to analyze effect of autogenic and handgrip relaxation on physical aspect (chemotherapy induced nausea and vomiting), psychological aspect (anxiety) in patients with breast cancer who undergo chemotherapy at PPLK (Cancer Service Development Center) RSUD dr. Soetomo Surabaya. Method: True Experimental with post-test only with control design. 72 respondents were involved and divided into 3 treatment groups and 1 control group. Research conducted within 3 weeks after chemotherapy until next chemotherapy session on each patients. Data were analyze used MANOVA and LSD (Least Significant Difference). Results: Autogenic and handgrip relaxation influence physical aspect and psychological aspect level significantly with p = 0.000 (p <0.05). LSD test showed no difference between autogenic relaxation, handgrip relaxation, and autogenic relaxation. Conclusion: Autogenic and handgrip relaxation have an effect on nausea vomiting and anxiety patients are able to adapt and control the body's response to be adaptive.